Library for the Digital Natives Generation: What to do - Halim, Siana; Wulandari, Dian; Kasih, Demmy; Felecia, Felecia; Inggrid, Inggrid (D3 Teknisi Perpustakaan Fakultas Vokasi Universitas Airlangga, 2016)
Nowadays, people does not need to go to the library for searching knowledge or information. World does change. We come to the new generation that so called as digital native generation. Information can be search through the gadgets on hands which connected to the internet. Then comes the question. Is the library still important? What the library should do? It is no wonder that most of the libraries have decreasing number of visitors as well as decreasing number of books that out of the shells. This paper describes the characteristics of the digital native, their habit in learning and reading books.Â It also summarized some discussions among the head of the three university libraries in Surabaya, i.e, Intitut Teknologi Sepuluh (ITS) Nopember Surabaya, Petra Christian University (PCU), Surabaya Universities (Ubaya). The results of the discussion shows, that library has to be changed so that they can accommodate the needs of the digital native. It is not only the place for borrowing books, but also the place for doing discussion, watching videos and listening to audios, and of course the online materials must be provided to encounter the decreasing visitors.